Hábitos de lectura y su incidencia en el aprendizaje de los niños del centro de educación básica “García moreno” de la parroquia Ricaurte cantón Urdaneta, provincia los ríos - Ayala Calberto, Íngrid Lissette (2015)
EXECUTIVE SUMMARY The purpose of this study was to investigate about reading habits in children and their impact on learning .Among the objectives that I identify methodological strategies used by teachers to form the habit of reading, analyzing the impact that produces habits reading as part of the development of learning. The theoretical framework turn around to know about reading habits, factors involved in reading, reading comprehension, poor reading habits, and learning the definition, process, and other types that will help them discover reading as a learning tool. The methodology was framed within the modality of feasible project because it allows manufactures and develops the proposed proposal and future solves the underlying problem, so that the research was applied field and literature. The technique used was the survey and direct observation considering the variables selected as my research objective. The study group was constituted by students corresponding to the third year of basic education and elementary teachers. It is intended that this project able to identify the impact of the reading habit in improving learning.